2022
DOI: 10.1007/s10639-022-10999-5
|View full text |Cite
|
Sign up to set email alerts
|

Serious game design model for language learning in the cultural context

Abstract: Digital learning environments have been gaining prominence during the last few years. In particular, the rising usage of mobile devices, including smartphones and tabs, has invited researchers to design and develop learning applications and games for such platforms. Mobile applications and games have been developed for learning languages like many other domains. However, most of these games are fun-based and lack a holistic design and development approach. Therefore, as a principal contribution, this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Given that sociocultural factors like family environments leave variable impacts on learner motivation, their influence on self-efficacy perceptions remains context-dependent (Ishaq et al, 2022;Kutuk, 2023). By extension, the prompts focusing on sociocultural orientations were aimed primarily at addressing how each participant felt respected by instructors from different backgrounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that sociocultural factors like family environments leave variable impacts on learner motivation, their influence on self-efficacy perceptions remains context-dependent (Ishaq et al, 2022;Kutuk, 2023). By extension, the prompts focusing on sociocultural orientations were aimed primarily at addressing how each participant felt respected by instructors from different backgrounds.…”
Section: Methodsmentioning
confidence: 99%
“…The research applying Bandura's (1986) Social Cognitive Theory (SCT) and Vygotsky's (1978) sociocultural theory shows that female learners in Saudi Arabia acquire L2 English differently when the motivational and engagement strategies favor self-efficacy cultivation. Whereas SCT posits that learning fulfills different purposes to achieve long-term goals, sociocultural theory addresses how normative structures and beliefs inform problem-solving abilities (Ishaq et al, 2022;Sun & Zhang, 2021;Tunçel, 2015). Bandura's theory further underscores how L2 English acquisition in female learners depends on individual motivation to overcome challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in the field of cultural propaganda, AI algorithms are at risk of sensitive privacy leaks. The risk of data leakage exists not only on cultural propaganda media platforms, but also on public Internet platforms [7][8]. For example, user comments and content analysis mechanisms used in social networks with huge amounts of information and presenting diverse and personalized content may have a direct impact on users' personal privacy, which in turn affects their personal image, opinion orientation, and value orientation.…”
Section: The Current State Of Development and Risk Challenges In The ...mentioning
confidence: 99%
“…Social networking sites have been growing over the last decade, and such forums have received much media attention. In Al Hasib (2022) and Ishaq et al (2022) , the authors have revealed that users often disclose a variety of information, including their name, age, gender, address, photo, etc . some even hide and compile this information.…”
Section: Related Workmentioning
confidence: 99%